Silver(I)-catalyzed denitrative trifluoromethylation of β-nitrostyrenes with CF3SO2Na. Issue 42 (19th October 2016) - Huang, Ping; Li, Yaming; Fu, Xinmei; Zhang, Rong; Jin, Kun; Wang, Wenxin; Duan, Chunying
Graphical abstract: Highlights: A novel silver(I)-catalyzed denitrative trifluoromethylation was developed. The cheap and economical trifluoromethyl reagent was used. The protocol to synthesize β-trifluoromethyl styrenes was delivered stereoselectivity. The approach was under mild conditions and showed wide substrate tolerance. Abstract: A novel and convenient approach to the synthesis of substituted β-trifluoromethyl styrenes via a silver(I)-catalyzed denitrative trifluoromethylation with CF3 SO2 Na under relatively mild conditions has been developed. This protocol delivered excellent stereoselectivity and showed wide substrate tolerance.